Aerobic power assessment by using a 10 min heart rate control running on treadmill - Wang, S. C.; Lin, H. F.; Wu, C. F.; Lin, B. N.; Wang, Y. S.; Huang, Y. J. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: This study evaluated the reliability and validity of a proposed 10 min running speed variance test (RSVHRC) in assessing aerobic power at which the intensity was controlled at 80% of age-predicted maximal heart rate (HR). METHODS: Forty-four college students (21 men and 23 women, age: 21±3 years, height: 166.6±7.9 cm, weight: 61.7±9.3 kg) were recruited to undergo 2 RSVHRC test trials, and a maximal exercise test at least 24 hours apart. The test consisted of a 3-min warm-up at 1.67 km/h, followed by adjusting speed up to either at 2.5 m/s or 2.78 m/s immediately depending upon onset HR after the warm-up. HR was monitored every 30 seconds and running speed was adjusted accordingly to maintain HR (±5bpm) for 10 minutes. RSVHRC was determined by the slope of distance/time relationship from 3rd to 10th min. RESULTS: Pair t-test showed that there was no significant difference between 1st (2.38±0.58 m/s) and 2nd trial (2.40±0.63 m/s). Intraclass correlation coefficient (ICC) score showed that RSVHRC was highly reliable (ICC=0.98, 95% CI=0.97-0.99). Coefficient of variation, standard error of measurement (SEM), and %SEM were 4.8%, 0.12 m/s, 5.02% respectively. Additionally, a Pearson product-moment correlation coefficient demonstrated 2 trials were correlated with maximal oxygen uptake (46.6±8.1 mL/kg/min) at r=0.74, 0.71 (P<0.05). CONCLUSION: In conclusion, 80%HRmax RSVHRC is an easy and highly reliable submaximal exercise test that provides good validity to assess aerobic power in young and healthy population, which can be applied on treadmill setting.